2018
DOI: 10.1001/jama.2018.14283
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Human Recombinant Alkaline Phosphatase on 7-Day Creatinine Clearance in Patients With Sepsis-Associated Acute Kidney Injury

Abstract: IMPORTANCE Sepsis-associated acute kidney injury (AKI) adversely affects long-term kidney outcomes and survival. Administration of the detoxifying enzyme alkaline phosphatase may improve kidney function and survival. OBJECTIVE To determine the optimal therapeutic dose, effect on kidney function, and adverse effects of a human recombinant alkaline phosphatase in patients who are critically ill with sepsis-associated AKI. DESIGN, SETTING, AND PARTICIPANTS The STOP-AKI trial was an international (53 recruiting si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
103
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(115 citation statements)
references
References 35 publications
3
103
2
1
Order By: Relevance
“…Although the study did not show a decrease in the primary endpoint of time corrected AUC of creatinine clearance for days 1 to 7, it did show decreased mortality in patients receiving alkaline phosphatase. More stage 3 AKI occurred in patients receiving alkaline phosphatase (11/111; 9.9%) than in those receiving placebo (5/116; 4.3%) 161. However, given the decreased 28 day mortality (17.4% in patients receiving 1.6 mg/kg compared with 29.5% of those in the placebo group), some possibility exists that although it is not a treatment for SA-AKI, recombinant alkaline phosphatase may play a role in the treatment of sepsis itself.…”
Section: Prevention and Medical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the study did not show a decrease in the primary endpoint of time corrected AUC of creatinine clearance for days 1 to 7, it did show decreased mortality in patients receiving alkaline phosphatase. More stage 3 AKI occurred in patients receiving alkaline phosphatase (11/111; 9.9%) than in those receiving placebo (5/116; 4.3%) 161. However, given the decreased 28 day mortality (17.4% in patients receiving 1.6 mg/kg compared with 29.5% of those in the placebo group), some possibility exists that although it is not a treatment for SA-AKI, recombinant alkaline phosphatase may play a role in the treatment of sepsis itself.…”
Section: Prevention and Medical Treatmentmentioning
confidence: 99%
“…Alkaline phosphatase has been thought to be effective through the direct dephosphorylation of endotoxin leading to attenuated inflammation and organ dysfunction and improved survival rates. A recent international, randomized, double blind, placebo controlled, dose finding adaptive phase IIa/IIb study included 301 adults with SA-AKI 161. In the dose finding portion of the trial, 120 patients were randomized to receive recombinant alkaline phosphatase in a dose of 0.4, 0.8, or 1.6 mg/kg of the drug or placebo, with 1.6 mg/kg being determined to be the optimal dose.…”
Section: Prevention and Medical Treatmentmentioning
confidence: 99%
“…In the first two trials, treatment with IAP improved renal parameters, and decreased serum CRP and interleukin (IL)‐6 levels, but had no effect on mortality. In a more recent large multicenter trial, the improvement of short‐term kidney function could not be confirmed …”
Section: Introductionmentioning
confidence: 86%
“…In humans, the effect of IAP on acute kidney injury during sepsis has been investigated in three phase II clinical trials . In the first two trials, treatment with IAP improved renal parameters, and decreased serum CRP and interleukin (IL)‐6 levels, but had no effect on mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation